2019
DOI: 10.30699/jidai.31.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dentin Surface Treatment Using a Non-Thermal Argon Plasma Brush on the Bond Strength of a Self-Adhesive Resin Composite

Abstract: Background and Aim: Improving the bond strength at the resin-dentin interface is an important challenge in adhesive dentistry. This study examined the effect of low-power, non-thermal atmospheric pressure plasma (NT-APP) treatments on the adhesion of a self-adhesive resin composite to dentin. Materials and Methods: In this experimental in-vitro study, buccal enamel of extracted bovine incisors was removed using a high-speed diamond bur. The specimens were randomly divided into two groups according to the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It seems that such chemical interactions between the old and new composite surfaces, may explain the adequate bond strength between them (34) . Moradi, Aida, et al 2019, assessed whether NTP application by itself has the potential to increase the bond strength of self-adhesive composites without using adhesives or dentin etching before the application of the composite resin (35) . Similarly, Huang, Chun, et al, 2007, found the treatment of dentin surfaces with NTP is a promising approach to improve the penetration of adhesive and resin bond strength to dentin (36) .…”
Section: Effect On Composite Repair and Bonding To Substructure Surfacesmentioning
confidence: 99%
“…It seems that such chemical interactions between the old and new composite surfaces, may explain the adequate bond strength between them (34) . Moradi, Aida, et al 2019, assessed whether NTP application by itself has the potential to increase the bond strength of self-adhesive composites without using adhesives or dentin etching before the application of the composite resin (35) . Similarly, Huang, Chun, et al, 2007, found the treatment of dentin surfaces with NTP is a promising approach to improve the penetration of adhesive and resin bond strength to dentin (36) .…”
Section: Effect On Composite Repair and Bonding To Substructure Surfacesmentioning
confidence: 99%
“…10 CAP is suitable to improve the adhesion of self-adhesive flowable resin composites to dentin. 11 The effects of nonthermal atmospheric pressure plasmas (NAPPs) on human mesenchymal stem cells isolated from periodontal ligaments (hPDL-MSCs) were analyzed. 12 The findings confirm that plasma applications do not have cytotoxic or any other negative effects.…”
Section: Introductionmentioning
confidence: 99%